An investigation into the Metal Grinding Process under Sub-Zero Temperature Cutting Fluid / Richard P. Daisley and Boppana V. Chowdary - Richard, P. Daisley; Chowdary, Boppana Veeraiah (UiTM Press, 2011)
The grinding process falls under the category of abrasive machining, which is a material-removal operation that involves abrasive grits interacting with the workpiece at high speeds and shallow penetration depths. In surface grinding, high heat is generated at the contact regions due to friction between the grit-chip and grit-workpiece interactions. This generated heat may damage the machined surface due to a sudden rise in temperature which induces phase transformations on the machined surface. These phase transformations lead to workpiece burns that drastically decreases the fatigue life of the job. Thus, the elimination of these burns is of considerable interest in this study. It is apparent that sub-zero temperature coolants would have the ability to bring about lower grinding temperatures than what is typically achieved under conventional fluids. In this study, a factorial experimental approach was used to investigate the effects of liquid carbon dioxide (LC02) on grinding stainless steel (SS304) material. The LC02 s performance was benchmarked against grinding under dry and emulsion coolant environments. Based on the experimental results it was found that under specific conditions, LCO2 proves to be a viable coolant alternative for grinding of temperature sensitive materials. Furthermore, under low depths of cut (0.012 - 0.025 mm) and table speeds (100 mm/s - 258.33 mm/s), LC02 restricts the occurrence of grinding burns.